Studi Perbandingan Daya Dukung Aksial Tiang Pancang Tunggal Persegi Berdasarkan Hasil Uji Pembebanan Statik (SLT) dan Uji PDA pada Pembangunan Apartemen Loftville City Kota Tangerang Selatan - Taqwa, Fadhila Muhammad Libasut; Muktadir, Redho; Hariati, Feril; Lutfi, Muhamad; Apriliyandi, Ande (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
Abstract: The deep foundation is one of the most important elements in the construction of high-rise buildings because the weight of the building will be fully borne by the foundation. This study aims to provide an overview of the prediction of the axial bearing capacity of single piles through a mathematical approach based on the results of the tests performed. The design axial bearing capacity is estimated through analysis of soil investigation results (N-SPT test results, DCPT test results, and laboratory investigation results), while the actual axial bearing capacity is obtained through interpretation of the Static Loading Test (SLT) results using the Davisson, Chin, and Mazurkiewicz, and the results of the PDA (Pile Driving Analyzer) load test were analyzed using the CAP-WAP application. The analysis was carried out on single piles with dimensions of 40x40 cm2, located in the Loftville City Apartment development project, South Tangerang City. Based on the results of the analysis that has been carried out, the planned axial bearing capacity is 131.3 tons, while the average carrying capacity based on the results of SLT interpretation on three tested piles using the Davisson, Mazurkiewicz, and Chin methods are 161.7; 205.4; and 98.8 tonnes. The results of the analysis are compared to the results of the PDA test, which shows a bearing capacity value of 290.1 tons, so the BCR values are 65.70% and 45.26% respectively. The BCR value is based on the results of the interpretation of the SLT test successively -respectively by 55.73%, 70.78%, and 34.06%. The BCR value which is not close to 100% may occur due to an error in determining the planned carrying capacity of 131 tons which is far below the actual carrying capacity value based on the PDA test results. The design carrying capacity value is then corrected to 100 tonnes and used as the 100% design load in the static load test so that the interpretation results also show BCR results that are not very accurate.